(untitled) (Research, Society and Development, 2022)
Flexibility is the ability to move one or more joints without any limitation of movement, and it can be hampered by the restriction of muscle fascia, which can present tensions and begin to stiffen, leading the body to loss of flexibility and spontaneity of movement. Myofascial Release is a massage technique capable of releasing these fascial tensions and promoting tissue relaxation, providing greater mobility and flexibility. The objective of this work was to verify the acute effects of Myofascial Release on the flexibility of the posterior chain of men and women who practice regular physical exercise. This is an intervention study, whose sample consisted of physically active men and women. A diagnostic evaluation was performed using the adapted sit-and-reach test, followed by the application of the Myofascial Release technique subsequent to the final retest/reevaluation. Comparisons were made between the means/medians for both sexes and compared to the intervention, as well as multivariate linear regression analyzes to verify the association of the study variables, at a significance level of α=0.05. The study sample had a mean age of 28.6±6.4 years. A statistically significant improvement was observed between the values ​​related to flexibility gains after the application of myofascial release in the studied sample. The application of the Myofascial Release technique provides an increase in the levels of acute flexibility of the posterior chain of men and women who practice physical exercise, being considered beneficial, indicating an efficient and promising alternative for the improvement of this physical capacity.